c y Mary Packard and the editors of Ripley Entertainment Inc. - Packard, Mary. (New York : Scholastic, 2002)
Did you know that a cockroach can live for a week without its head? or that silk is made out of caterpillar spit? Bizarre bugs is crawling with hundreds of incredible facts like these. Get ready to be grossed out.
Keywords: Insects -- Miscellanea -- Juvenile literature; Curiosities and wonders -- Juvenile literature